Sistem Pendukung Keputusan Pada Aplikasi Penyedia Layanan Internet Terbaik Menggunakan Metode Multi Factor Evaluation Process - Dwi Nurul Huda; Muhammad Tri Margianto (Jurnal Bangkit Indonesia, 2022)
This research is motivated by the condition of the choice of internet service provider, it is not uncommon for prospective consumers to find it difficult to determine the internet package service that suits their needs. This is because consumers need to consider various criteria before deciding which internet service provider to use. In line with that, consumers can use the concept of a decision support system by using a computerized service system based on a website as a tool and makes it easier to determine the most ideal internet service provider (ISP) which will be used in wireless networks in the home environment. One of the methods in the selection of decisions is the Multi Factor Evaluation Process method. Or commonly abbreviated as the MFEP method. MFEP is a method that has minimal and simple calculations. This research using the MFEP method is carried out to determine internet service providers according to the requirements or criteria that have been determined. The research is that the system that will be made later will provide convenience in determining the best internet service provider. Provide recommendations to users according to the criteria. This election system is an application program that has been computerized, thus helping prospective users to find the service provider they want.